EFFECT OF EDUCATION AND TRAINING (DIKLAT / BIMTEK), UNDERSTANDING OF REGIONAL FINANCIAL ACCOUNTING SYSTEMS (SIMDA) ON PERFORMANCE OF REGIONAL FINANCIAL MANAGEMENT - Nenden Restu Hidayah (BIMA Journal (Business, Management, & Accounting Journal), 2020)
This study examines the effect of Education and Training (Diklat / Bimtek), Understanding of the Regional Financial Accounting System (Simda) on the Performance of regional financial managers. This research was conducted on 60 regional financial managers in 33 Regional Government Work Units (SKPD) Bengkulu City Government. This study collected data by giving questionnaires to respondents. Research data were processed using the SPSS program.The results of the study prove that Education and Training (Diklat / Bimtek), Understanding of the Regional Financial Accounting System (Simda) has a positive effect on the performance of regional financial managers. This proves that the better the management carried out by the regional government towards Diklat / Bimtek, the understanding of Simda which is owned by the regional financial managers in the SKPD, the better the performance of regional financial managers. Bengkulu City regional government to continue to improve the existing Diklat / Bimtek model, together with increasing understanding of Simda towards local government SKPD.